Sway of the Ottoman Empire on English identity in the long Eighteenth Century - Kugler, Emily M. N. (Brill's studies in intellectual history, 2012)
By focusing on eighteenth-century English textual representations of the Ottomans, we can observe the turning point in public perceptions, the moments when English subjects began to believe British imperial power was a reality rather than an aspiration.